Association between motor development of typical children and head and trunk alignment - Martinello, Micheli; Louzada, Maria W.; Martins, Tamiris B.; Rafael, Aline D.; Santos, Gilmar M.; Johnston, Cintia (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Among the typical motor development, it is considered the neck control as being of great importance. Although there is no consensus of the best positioning for stimulation of neck control, it is clear in the literature the positive association between the prone position and the typical motor development according to the age of infants. Objective: To investigate the association between the kinematic variables related to neck control and bracing with age and motor performance in the prone position of typical children. Methods: 30 children participated in the study. Motor development was assessed by Alberta Infant Motor Scale (AIMS), and the alignment of the head, trunk and upper limb was analyzed through kinematic analysis in the prone position. Results: with the association of the variables: age, AIMS in the prone position and the kinematic variables (inclination of the head, trunk extension, shoulder angle and elbow angle), was observed that the increase in age and the best performance in the prone position corresponding to the inclination of the head. The trunk and elbow extension also increases. Conclusion: there was a positive association between the variables age and motor performance in the prone position of typical children, with kinematics variables the inclination of the head, the trunk and the elbow extension.